Experience of Kurdistan province of Iraq in light of the development of economic and social indicators for sustainable development - فتاح, عبد الجبار محمود; حمد, ايوب انور (Journal of Economics and Administrative Sciences, 2015)
Reflect the sustainable development of the interaction of three key elements are the economic component and the social component and the environmental component while focusing economic component to achieve economic growth and focuses social element to achieve social justice in the distribution of income and achieve prosperity, the environmental component related fields and including emphasizes the protection of the environment and to ensure the continuation and sustainability of resources physical, biological and form in which it believes the interaction required for development process real and effective and sustainable, and is considered the province of Kurdistan Iraq of important areas where the movement of developmental mounting but surrounded by challenges enormous, which requires work to drive development in the right direction and try to curtail the impact of the challenges faced by, to inform the development paths and ranges, it turned out during the previous phase and the extent of qualification for the continuation and sustainability has to be dealt with some of the indicators related to the process of sustainable development in the economy of the region in order to detect the nature and shape of the region and experience the developmental stages. Hence the importance of research experience in the Kurdistan Region - Iraq's development in light of the economic and social indicators for sustainable development, where economic indicators proved there is an improvement in the standard of living and social indicators have proved that there is an improvement in some aspects and underdevelopment in some social indicators for sustainable development